The Management of Inheritance in Community Economic Development: Islamic Economics Perspective - Taufiq Kurniawan (Universitas Muhammadiyah Surakarta, 2025)
Inheritance is one of the instruments of wealth distribution that is clearly regulated in Islamic law. A fair and proportionate inheritance distribution mechanism not only has legal implications but also significantly impacts the community's economic development. This article discusses inheritance management from an Islamic economic perspective, emphasizing the functions of distribution and social justice and their role in strengthening the financial structure of the family and society. This study uses a qualitative-descriptive approach based on the study of literature from the Qur'an, Hadith, and the views of fiqh scholars as well as contemporary Islamic economic literature. The results of the discussion showed that inheritance management in accordance with sharia can reduce social disparities, strengthen family solidarity, prevent the accumulation of wealth in a few parties, and encourage a healthy circulation of wealth in society. Thus, inheritance management is not only a private family affair, but also has a real contribution to the economic development of a just society.